An LMI robust predictive control approach applied to synchronous machines - Silva, Cláudio Homero Ferreira; Henrique, Humberto Molinar; Lopes, Luis Cláudio Oliveira; Gomes, Luiz Renato (Revista Ciências Exatas, 2008)
Small hydroelectric power plants basically use classical and simplified algorithm strategies applied to the control of the process. However, it is known that robust model predictive control can guarantee stability and improve performance in model based uncertain systems. This paper addresses this problem and applies to a hydro power plant control a set of control techniques such as the classical model predictive control and an LMI based robust model predictive control to ensure the guarantee of robust stability for certain class of uncertainties. The paper presents simulation results for Martins Hydro Plant (4 x 2,75 MVA) located at Uberlândia(MG)/Brazil.